Upaya Peningkatan Pengetahuan Keluarga Untuk Mencapai Keluarga Bahagia Sejahtera Melalui Program Keluarga Berencana (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Planned parenthood is a program carried out to help regulate the spacing of children's births, and regulate pregnancies to create a quality family. Good knowledge is an asset in family planning programs, however, there are still some couples of childbearing age who have not used contraception because the knowledge of couples of childbearing age is still inadequate about the importance of family planning to regulate birth spacing they also have obstacles in choosing the right contraceptive. The respondents in this activity were 15 couples of childbearing age. This service to the community is carried out through the delivery of health information. Respondents assessed their level of knowledge before and after health education by filling out a questionnaire. The results obtained were the level of knowledge before being given health education, 8 (53%) people had sufficient knowledge, and 7 (47%) people had insufficient knowledge. After being given health education, 15 (100%) respondents' knowledge was good. Health education about family planning helps people create happy and prosperous families
Keywords: couples of childbearing age, planned parenthood, health education